Disseminated Strongyloidiasis in a Patient With Lupus Nephritis - Muhammad Abu-Rmaileh; Melanie Holtrop; Andrea Amaro; Niraj Madhani; Roma Mehta; James Lyons (Annals of Internal Medicine: Clinical Cases)
Strongyloides stercoralis is a helminth that can parasitize humans and manifests with numerous symptoms. Immunocompetent patients have a less virulent course, whereas immunocompromised patients can have high mortality rates. Our case is a 43-year-old woman with lupus nephritis receiving prednisone who presented with vomiting, diarrhea, and worsening renal failure. Despite various treatments, she developed a partial small-bowel obstruction, renal failure, and pancytopenia. Bronchoscopy revealed Strongyloides larvae. Her infection resolved after treatment with ivermectin. High suspicion of Strongyloides in specific patient populations is critical in making a life-saving diagnosis.